Pendugaan Umur Simpan Jambu Kristal (Psidium guajava L.) Terolah Minimal menggunakan Metode ASLT (Accelerated Shelf Life Test) Model Arrhenius - Eva, Yulia; Syska, Kavadya; Nurhayati, Asti Dewi (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Shelf life prediction plays a crucial role in ensuring the quality and safety of food products. The increasing popularity of minimally processed crystal guava (Psidium guajava L.) in the food industry highlights the need to understand and optimize its shelf life. Minimally processed products offer advantages by preserving the sensory qualities and nutritional value of fruits while minimizing the use of preservatives and heat treatments that may compromise the inherent characteristics of the fruit. This research aims to assess the quality changes in minimally processed crystal guava using the Accelerated Shelf Life Test (ASLT) with the Arrhenius model and to estimate its shelf life under different storage conditions. The RESEARCH utilized a Completely Randomized Design with two factors: packaging types (PP, HDPE, Wrapping) and storage temperatures (10˚C and 30˚C). The parameter under investigation was water content. The findings revealed that at 10˚C, HDPE packaging exhibited the highest water content on the 9th day compared to Wrapping packaging, registering 23.67. At 30˚C, the highest water content was observed with HDPE packaging, reaching 33.27%, while Wrapping packaging recorded the lowest at 18.6%. These results provide valuable insights into the influence of packaging and storage conditions on the water content of minimally processed crystal guava. The practical implications of this research extend to the food industry, offering guidance for optimizing distribution and inventory management based on the predicted shelf life. Understanding these factors enhances the efficiency of production planning and ensures that the product maintains its quality throughout the desired storage period, meeting consumer expectations for fresh and high-quality produce.